Natura 2000 in the Light of Opinions of Chief Officers and Councillors of Communes Covered by the European Ecological Network - Guzal-Dec, Danuta; Zwolińska-Ligaj, Magdalena (Instytut Rozwoju Wsi i Rolnictwa Polskiej Akademii Nauk, 2010)
The paper presents the attitudes of the representatives of self-governments in communes covered by the Natura 2000 network towards the problems of environmental protection and the rank of environmental matters in the process of managing the development of communes, with special emphasis on the opinions about the impact of the Natura 2000 network on the development of local economies. The surveyed representatives of local councils have expressed both negative and positive opinions on the effects of their communes’ inclusion in the Natura 2000 network. It seems that negative opinions on Natura 2000 have their source in the lack of information and failure to ensure self-governments active role in the process of delimitation of areas included in the Natura 2000 network. It should be noted that the representatives of local councils are aware of the potential role of the natural environment’s resources and properties in the creation of the communes’ development but at the present stage of its functioning the Natura 2000 network arouses serious reservations that obscure the potential advantages.
Keywords: self-government bodies in communes; Natura 2000; development of communes; opinions of the representatives of local councils concerning the Natura 2000 areas